AGN feedback by relativistic jets. Issue Volume 10:Issue S313(2014) (24th March 2015) - Bicknell, G. V.; McNamara, B. R.; Nawaz, M. A.; Sutherland, R. S.; Umemura, M.; Wagner, A. Y.
Abstract: Feedback provided by relativistic jets may be effective in shaping the galaxy luminosity function. The quenching mode (quasar mode) at redshifts 2-3 potentially disperses gas in star-forming galaxies. The maintenance mode (radio mode) heats the gas in galaxy clusters counteracting cooling flows. A number of authors have examined the effect of relativistic jets in dispersing clouds in the kpc-scale inhomogeneous interstellar medium of evolving galaxies. We have also investigated a particular case of maintenance-mode feedback in our simulation of the iconic radio galaxy / cooling flow cluster Hydra A. Modelling of the knots produced by the jets in the inner 10 kpc provides an estimate of 0.8 – 0.9 c for the velocities of the jets in agreement with other velocity estimates for FR1 jets. The addition of jet precession provides realistic simulations of the morphology of the Hydra A radio source and raises interesting questions as to the role of black hole and disk precession, in general, in galaxy formation.